2021
DOI: 10.1089/mdr.2020.0514
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Colistin- and Tigecycline-Resistant Klebsiella pneumoniae ST29 in Municipal Wastewater Influents in Japan

Abstract: The aim of this study was to investigate the presence of colistin-and/or tigecycline-resistant Klebsiella spp. in influents from four wastewater treatment plants (WWTPs) which partly reflect the gut microbiome of human populations. Colistin-and tigecycline-resistant K. pneumoniae isolates (K30/ST29) were detected four times from the WWTP A for three months. Disruptions of the mgrB and ramR genes by ISEc68 and ISKpn21, respectively, were identified in those four isolates. They also shared the IncL/M 86,197-bp p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…pBM413 has IS1394 region inserted into the ISCE1 - qnrVC6 - ISCR1 array. The array of ISEc28 - armA - ISEc29 - msr(E) - mph(E) was reported in Klebsiella pneumoniae , 36 which unlike our study, omits IS1394 . The similar resistance architecture between pKB-PA_F19-4 and pBM413 implies that these plasmids may have the same origin.…”
Section: Discussioncontrasting
confidence: 68%
“…pBM413 has IS1394 region inserted into the ISCE1 - qnrVC6 - ISCR1 array. The array of ISEc28 - armA - ISEc29 - msr(E) - mph(E) was reported in Klebsiella pneumoniae , 36 which unlike our study, omits IS1394 . The similar resistance architecture between pKB-PA_F19-4 and pBM413 implies that these plasmids may have the same origin.…”
Section: Discussioncontrasting
confidence: 68%
“…Other studies have also reported occurrence of TGC and colistin co-resistance among K. pneumoniae isolates belonging to ST37 and ST11 ( Taniguchi et al, 2017 ; Xu et al, 2020 ). A recent study also reported detection of colistin and TGC-RKP (ST29) in municipal wastewater influents from Japan ( Hayashi et al, 2021 ). All human TGC-NSKP isolates showed co-resistance to carbapenems and carried genes encoding for two different carbapenemases.…”
Section: Discussionmentioning
confidence: 96%
“…The emergence of CRKP which showed resistance to colistin was recorded in several reports. 44,45 The bright spot in our results was the absence of colistin-resistant phenotypes, which have high lethality. Alarmingly, an extensive variability was recorded among our isolates.…”
Section: Discussionmentioning
confidence: 69%